2001
DOI: 10.1021/jo015775k
|View full text |Cite
|
Sign up to set email alerts
|

Heterobuckybowls:  A Theoretical Study on the Structure, Bowl-to-Bowl Inversion Barrier, Bond Length Alternation, Structure-Inversion Barrier Relationship, Stability, and Synthetic Feasibility

Abstract: Hybrid density functional theory (DFT) calculations at the B3LYP/cc-pVDZ level have been performed on a series of heterobuckybowls, 3X, C(18)X(3)H(6) (X = O, NH, CH(2), BH, S, PH, PH(3), Si, SiH(2), and AlH). The minimum energy conformations and the transition states for bowl-to-bowl inversion, where the geometry is bowl shaped, are computed and characterized by frequency calculations. The geometries of heterotrindenes, 2X, C(12)X(3)H(6) (X = O, NH, CH(2), BH, S, PH, PH(3), Si, SiH(2), and AlH), were obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 85 publications
2
37
0
Order By: Relevance
“…Heterobuckybowls doped by larger heteroatoms other than carbon such as S, Si and Sn exhibited less curvature, resulting in shallower bowls or planar structures [16][17][18] . In contrast, azabuckybowls doped by nitrogen atoms, which are smaller than carbon atoms, are predicted by calculations to exhibit more curvature with deeper bowl depth than all-carbon bowls 14 . Synthesis of such a highly strained bowl structure has been a challenging task for a long time 19 .…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Heterobuckybowls doped by larger heteroatoms other than carbon such as S, Si and Sn exhibited less curvature, resulting in shallower bowls or planar structures [16][17][18] . In contrast, azabuckybowls doped by nitrogen atoms, which are smaller than carbon atoms, are predicted by calculations to exhibit more curvature with deeper bowl depth than all-carbon bowls 14 . Synthesis of such a highly strained bowl structure has been a challenging task for a long time 19 .…”
mentioning
confidence: 68%
“…Buckybowls have attracted much attention not only as model compounds for fullerenes, but also for their own chemical and physical properties [10][11][12][13] . In contrast to nitrogen-doped fullerenes and CNTs, nitrogen-doped buckybowls, azabuckybowls, still remain unknown except for some theoretical studies 14,15 . Doping of nitrogen to the aromatic skeleton is expected to modulate the curvature, bowl inversion barrier, and physicochemical properties.…”
mentioning
confidence: 99%
“…Theoretical studies suggested that doping of nitrogen will lead to deeper and curved bowl depth compared to the all-carbon counterparts [77]. Sakurai and co-workers reported the first chiral nitrogen-doped buckybowl (Scheme 3) [12].…”
Section: Asymmetric Synthesis Of Buckybowl and Azabuckybowlmentioning
confidence: 99%
“…Several computational studies have been carried out on sumanene and its dimer [13, and references therein] and the monomers of heterosubstituted sumanenes [22][23][24][25][26][27][28]. These studies focused on the monomer geometries, bond alternations, and bowl inversion.…”
Section: Introductionmentioning
confidence: 99%